Women's experiences of surviving severe obstetric complications: a qualitative inquiry in southern Ghana - Ruby Elikem Afi Amegavluie; Mary Ani-Amponsah; Florence Naab (BMC, 2022)
Abstract Women who survive severe obstetric complications (SOC) have health and well-being issues even up to 1 year postpartum and have challenges in their quality-of-life (QoL). However, little is known about their predicaments. This study aimed to describe the impact of severe obstetric complications on women's QoL and well-being after surviving severe obstetric complications. Using the WHO standards for near-miss, twelve (12) women who survived severe obstetric complications were recruited between January and March 2019. The study adopted a qualitative approach with an exploratory descriptive design to explore the experiences of women who survived SOC in Southern Ghana. The participants were purposively sampled and were interviewed face to face in their homes and healthcare facility after discharge from the Hospital. Recorded interviews were transcribed and analyzed. Two (2) major themes and nine (9) sub-themes emerged. The findings revealed that women who suffered SOC are unable to perform functional activities, have financial constraints, residual hypertension, signs and symptoms of anaemia, pain, and mostly have difficulty in sleeping due to fear of death when they fall asleep. Anxiety, sadness, and emotional trauma was a common phenomenon. The study findings offer insights and directions on measures to improve the care and QoL of women who have survived severe obstetric complications in Ghana.